Análisis de la gestión del talento humano del gobierno autónomo descentralizado municipal del cantón Pindal - Calderón Obaco, Elisa Yomar (2016)
Human effort is vital to the functioning of any organization, if the human element is willing to provide effort, the organization will march, otherwise, stop. Hence to every organization should pay primary attention to personal (human talent), that is why it has developed this thesis project was carried out in the Municipal GAD Pindal canton of Loja Province located in the Celica streets and Alamor administered by the current mayor Economist Jumbo Lapo Bolívar 2009-2014. In the aforementioned institution has verified that there are shortcomings in the improper application of appropriate techniques for management of human talent, especially in the process of admission and employment recruitment, selection, recruitment, induction and training of staff which causes an inconvenience development Municipal entity in so you do not have an efficient staff to hold those positions . This is the main difficulty in the progress of public and private organizations that do not apply the technical processes of admission and employment correctly, for this reason it was undertaken to decide this issue of research in order to contribute to the body of the Municipal GAD Canton Pindal serve as a tool for improvement for good personnel administration. To run the research was performed by a problematic, introduction, literature review, then justifying the object of study considering general and specific objectives, methodology, resources, materials, methods and 6 techniques, the results I got them through direct observation, surveys servants and officials and workers interview the head of talent by which necessary information is obtained in order to run a diagnostic to verify facts about the talent management of the Municipal Institution. Based on the survey of staff GAD 14% entered the recruiting process and while 86 % were admitted for other processes, it should be emphasized that most of the personnel entered the institution does not by political will and carried out the process of admission and employment. Later this information the proposal will contribute to better management of human talent in this organization is made, this includes the Technical Admission and Employment as: recruitment through the media using the necessary elements to make the ad as is logo, name of institution, the charge that is required profile for the position or vacancy, giving the company and the direction of the industry because we only provided by friends or relatives. In what has to do with the selection perform the job application form, interviews, tests and investigations, as currently done by the interview. As for proposed legally make contracts ie by a signed contract as it is done verbally. It further proposes the welcome manual which state history, services offered, regulation, main functions , a training on topics such as customer service, human relations, how to prevent accidents, values, etc., and a plan of motivation through vouchers, giveaways, celebrations among others, to the staff working in the town. Finally the respective conclusions and recommendations accompanying bibliography of research work will be presented.